Risk factors associated with prolonged mechanical ventilation after surgical patent ductus arteriosus ligation in preterm infants. (2nd October 2022) - Seo, Yu Mi; Sung, In Kyung; Yum, Sook Kyung
Abstract: Background: One of the main pathophysiologies of a hemodynamically significant patent ductus arteriosus (hsPDA) involves pulmonary over-circulation. However, PDA treatment does not present with uniform effects on pulmonary outcomes. We aimed to evaluate the clinical characteristics – in particular, respiratory parameters – associated with prolonged mechanical ventilation after PDA ligation. Methods: Preterm infants ≤32 weeks gestation were included in the study. Infants who underwent PDA ligation were grouped depending on whether the infant successfully was extubated ≤14 d after ligation or required prolonged invasive mechanical ventilation >14 d after ligation. The clinical characteristics, including the parameters concerning the respiratory illness severity and hemodynamical significance of PDA shunt, were compared between the two groups. Results: Among 172 preterm infants, 36 (20.9%) infants underwent surgical PDA ligation. Fifteen (41.6%) infants were successfully extubated at ≤14 d after ligation, and 21 (58.3%) infants required prolonged invasive mechanical ventilation for >14 d after ligation. In the univariable analysis, the infants who required prolonged mechanical ventilation was significantly smaller in terms of gestational age (GA) and birth weight and tended to present a greater respiratory illness severity [represented by the use of high-frequency oscillatory ventilation (HFOV) and greater RSS (respiratory severity score)/kg] with a larger PDA size prior to PDA ligation. In the multivariable logistic regression analysis, peak preoperative RSS/kg ( p  = 0.012, OR = 0.207, 95% CI = 0.060–0.706) was the only significant factor associated with prolonged mechanical ventilation after PDA ligation. Conclusion: Preterm infants with the compromised respiratory condition may be prone to prolonged mechanical ventilation after PDA ligation. The respiratory status during the early phase of life should be considered when evaluating the effect of PDA treatment. With an extended view, distinguishing infants with such risk factors may lead to more polished treatment strategies toward hsPDA.